Analisis Penggunaan Teknik Editing Pada Music Video Stray Kids Thunders - Khairi, Ananda Salsabila; Amri, Hairul; Bancin, Haryanzelina; Ikhwan, Ali (CV. Information Technology Training Center - Indonesia (ITTC), 2023)
Video is the latest communication media which is a part of electronic media in digital form. Video comes with the characteristics of a film, and video can also be integrated into the world of music, which is like being used as a music video. Korean pop (K-Pop) is a term that is no longer common for lovers of Korean pop music. K-Pop or Korean pop is music that is currently popular and originates from South Korea. The development of K-Pop music is spreading very quickly among young Indonesians. One of the popular Korean pop groups today is Stray Kids with one of their songs entitled Thunders. The purpose of this study is to find out the editing process used in the music video. This research uses a qualitative descriptive type and the method used is observation. Then the results of this research are obtained, namely that readers understand some of the terms in editing and can implement them into videos that you want to make look attractive.